Exposure risk of household insecticide: identification of the knowledge, attitude and practice levels among Kuantan population, Pahang - Abd Hamid, Abdul Alif; Md Isa, Muhammad Lokman; Lee, Siew Pien; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin; Abd Hamid, Hamizah (Faculty of Medicine and Health Sciences, 2021)
Introduction: Dengue is a mosquito-borne flu-like illness which massively caused Malaysian morbidity and mortality. The prevalent of cases influenced by high humidity climate and urbanization which enhances the mosquito breeding. Thus, the utilization of household insecticide became a necessity among the urban community especially in the Kuantan city, Pahang. The insecticide is made of type 1 pyrethroids chemicals that are recognized to be safe. However, there were reported insecticide intoxication cases that suggested insufficient studies on insecticide usage and its exposure effects. Hence, the study aimed to assess the community’s knowledge, attitude and practice (KAP) level upon household insecticide and its associated factors among Kuantan’s public. Method: A cross-sectional survey was conducted among 199 respondents via a self-administered questionnaire concerning sociodemographic and KAP’s domain data was distributed and collected. Results: Most respondents had adequate KAP scores. Statistical analysis confirmed that marital status group (p = 0.047) affected knowledge singles and married person had higher knowledge score. There were significant association between females with levels of knowledge (p = 0.003) and attitude (p = 0.024). A strong positive correlation between knowledge and attitude (r = + 0.800, p = 0.010), between knowledge and practice (r = + 0.760, p = 0.010), and a good positive correlation between attitude and practice (r = + 0.740, p = 0.010). Conclusion: The finding of Kuantan public’ KAP data can be used as a reference to formulate effective health promotion intervention to reduce the insecticide exposure risk among wider public community.